THE APPLICATION OF “BLENDED LEARNING” IN TEACHING ENGLISH SKILLS FOR 1ST YEAR ENGLISH MAJOR STUDENTS AT UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES (ULIS, VNU) = ỨNG DỤNG PHƯƠNG PHÁP DẠY HỌC TÍCH HỢP TRONG GIẢNG DẠY KỸ NĂNG TIẾNG CHO SINH VIÊN NĂM NHẤT CHUYÊN NGÀNH TIẾNG ANH TẠI TRƯỜNG ĐẠI HỌC NGOẠI NGỮ - Trần, Thị Khánh Linh (2020)
The application of “Blended Learning” in teaching English skills for 1st year English major students at University of Languages and International Studies. In the 21st century, technology has been spreading at a dizzy pace in almost all areas of our life. In educational field, it is claimed that technology should be brought into operation within any subjects, including languages. In the context of teaching and learning English skills at Faculty of English Language Teacher Education (FELTE), University of Languages and International Studies (ULIS), the research aims at identifying the acknowledgement and level of application of technology in language teaching at the faculty. The research is hoped to reveal the great influence and multiple benefits of applying technology in teaching and learning English linguistic skills.